Strategic Management of Santri in Enhancing Religious Moderation: A Study at Quranic Junior High School Darul Fattah - Musdalifah, Ulfani; Amiruddin; Fauzan, Ahmad (Journal of Advanced Islamic Educational Management, 2025)
Harmonious relationships between teachers, students, communities, and the surrounding environment This study aims to explore the strategy of santri management in strengthening religious moderation at Quranic Junior High School Darul Fattah, South Lampung. Using a qualitative case study approach, data were collected through interviews with school leaders, teachers, and students, as well as through observation and documentation. The findings reveal that religious moderation is strengthened through structured santri orientation programs, integrated coaching and development aligned with the Pancasila Student Profile Project (P5), and a graduation system that emphasizes both academic and religious-moderation competencies. The school also implements a life skills approach that instills values of tolerance, empathy, and inclusivity through extracurricular and character-based management strategies. This study concludes that structured santri management plays a critical role in fostering a moderate Islamic identity among students. The findings offer a model for other pesantren-based institutions aiming to integrate religious moderation into their educational practices.